ERROR ANALYSIS IN THE NARRATIVE WRITING PRODUCED BY STUDENTS OF SMP NEGERI 4 MALANG - PUTRI, DYANARA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Nowadays, English is one of the international languages used in the world. However, Indonesians do not use English in their daily life. Although English is aforeign language, Indonesian students, from elementary up to university shouldlearn English because English is very important in this globalization era. In theprocess of learning, Indonesian students surely make errors. It is understandable since the rule of Bahasa Indonesia and English is different. This research aims: (1) to identify the types of errors and (2) to find the most frequently error in the narrative writing produced by the eighth grade students of bilingual class of SMP Negeri 4 Malang.This research is designed by using descriptive qualitative research anddocument analysis to answer the problems of the study. The data were collectedfrom the thirty two narrative writing produced by the eighth grade students ofbilingual class of SMP Negeri 4 Malang. In collecting the data, the researcherasked the students to write a narrative paragraph about 150 until 200 words with a topic chosen in 100 minutes. The researcher analyzed the data using the theory from Dulay, Burt, and Krashen (1982) about surface strategy taxonomy.The results of this research showed that the students did some types oferrors when they wrote a narrative writing. Those errors are omission, addition,misformation, and misordering. Omission was divided into some parts namely,omission of preposition, omission of ‘be’, omission of plural marker, andomission of article. Then, addition was divided into two types namely, addition of‘be’ and addition of verb. Misformation was also divided into two types namely,misformation of ‘be’ and misformation of verb. The last is misordering.The researcher suggests to the next writers who want to conduct thesimilar research use the different object and analyze the errors with other theories. Another suggestion is to use the same theory but with the different object like textbook or article for the data.